BLACK MOUNTAIN COLLEGE SEMESTER: (RE) LEARNING EXPERIMENTATION IN ARTS AND CULTURE EDUCATION - Schumann, William (PEOPLE: International Journal of Social Sciences, 2024)
Black Mountain College Semester (BMCS) was an interdisciplinary teaching and public education project implemented in 2018 at Appalachian State University in mountainous western North Carolina, USA. BMCS drew over 30,000 attendees and participants despite the rural character of the project area. Based on the experimental pedagogy of the influential Black Mountain College (1934=1963), the ten-month, multi-sited BCMS project sought to create intentional spaces of interdisciplinary collaboration–bringing the humanities, social sciences, arts, and design sciences into conversation–but more importantly, to facilitate the development of experimental cross-disciplinary and academic-public collaborations independently of the project leadership team. This paper offers a brief overview of Black Mountain College, followed by a discussion of the decentralized project design and the analysis of two project case studies. BMCS planning started with the original College principles of experiential and democratic learning philosophy, which invited participation and collaboration across hierarchical academic silos. Fundamentally, the concept of independent inquiry, not specific project outcomes, drove this process. Faculty, administrators, staff, non-profit leaders, educators, and the public contributed to events as varied as exhibitions, public talks, workshops, publications, theater, music, and curriculum design across four project sites. The first case study describes an interdisciplinary faculty fellowship program, created by project leaders, to support the application of learning concepts from Black Mountain College in university courses. The second describes the process of creating an interactive website linked to three museum exhibitions that extended BMCS into public domains and extra-academic spaces of learning. Broadly, this paper analyzes the process of co-creating methods of experiential learning on and beyond a university campus. Project assessment data is utilized to contextualize public responses to BMCS and discuss future directions for the project.